A STUDY ON THE CAUSES AND CONSEQUENCES OF ACCIDENTS WITH CRANES FOR LIFTING AND MOVING LOADS IN INDUSTRIAL PLANTS AND CONSTRUCTION SITES OF THE RUSSIAN FEDERATION - Tomakov, Vladimir Ivanovich; Tomakov, Maksim Vladimirovich; Pahomova, Ekaterina Gennadievna; Semicheva, Natalia Evgenievna; Bredihina, Natalia Vladimirovna (Journal of Applied Engineering Science, 2018)
The article is devoted to the investigation of the causes and consequences of crane lift crashes at industrial facilities and construction sites in the Russian Federation. The distribution of accidents by types of lifting cranes and accidents by occupations of deceased workers is shown. Accidents are categorized for their reasons. The causes of most accidents are the "human factor": low technological discipline, inadequate staff qualifications, poor-quality installation and untimely equipment repair. Also, the level of industrial safety is affected by technical, organizational and financial problems at enterprises. The main reason for the decline in the level of industrial safety is a significant amount of equipment that has fulfilled its calculated resource